Research on China's Monetary Policy and Stock Market Price-volume Relationship Based on TVP-SV-VAR Model. Issue 4 (February 2020) - Hu, Yibo; Lai, Yujie
Abstract: A time-varying VAR system model of monetary policy and stock market is established in this paper for analyzing the dynamic correlation and response mechanism between monetary policy variables and stock market variables. It is found that the influence of interest rate on stock price has experienced a period of "irrelevance, positive correlation and negative correlation" in 20 years. According to the uniformly-spaced impulse response, it is found that China's monetary policy has real effect in the short term, but lacks long-term sustainability. The stock reform in 2005 can be regarded as an important time node to change the relationship of stock market price-volume in the past two decades. For most of the period after the stock reform, stock prices have a positive impact on stock market turnover and stock market returns.